A new correlation of viscosity and conductivity for the polyelectrolyte solutions of poly(sodium styrene sulphonate) (PSSNa) in N, N-dimethylformamide + water. (4th March 2021) - Cherif, Emna
ABSTRACT: The effects of temperature and concentration on the reduced Walden's law of solutions of poly(sodium styrene sulphonate) (PSSNa) in N, N-dimethylformamide + water (DMF/W) were examined at various temperatures between 20°C and 60°C and concentration levels between 0.1 and 1 g/l. The effects of temperature were described by an Arrhenius-type equation. The intrinsic Walden product [ ση ] and the Huggins constant of Walden, kση, were calculated and studied. Then, d(ln [ ση ])/d(1/ T ) were calculated as the parameter for chain ﬂexibility and molecule conformation. These results showed that the intrinsic Walden's law product does not decrease linearly with increasing temperature for all concentrations of PSSNa.